The Examination of Picture and Text Interference on Literature Lesson (Training and Practice : Journal of Educational Sciences, 2012)
The study interprets works the text of which also include allusions, descriptions of fine artworks (paintings, sculptures, photographs, comic strip), or fine artworks infiltrated as visual inter-text into their body text. The study of the function of the fine artworks fulfilled in the text, the mythical and religious concerns of the works of art embedded in the text enriches the interpretation of the texts with new viewpoints and makes literature teaching true to life. The analysed texts, abundant in graphical references, are included in the Hungarian language and literature curricula of the Serbian primary and high schools as texts intended to adaptation, as obligatory or recommended home readings.